History of global burden of disease assessment at the World Health Organization - Colin D. Mathers (BMC, 2020)
Abstract Background The World Health Organization collaborated in the first Global Burden of Disease Study (GBD), published in the 1993 World Development Report. This paper summarizes the substantial methodological improvements and expanding scope of GBD work carried out by WHO over the next 25 years. Methods This review is based on a review of WHO and UN interagency work relating to Global Burden of Disease over the last 20 years, supplemented by a literature review of published papers and commentaries on global burden of disease activities and the production of global health statistics. Results WHO development of global burden of disease work in the Millenium Development Goal era resulted in regular publication of time series estimates of deaths by cause, age and sex at country level, consistent with UN population and life table estimates, and with cause-specific statistics produced across UN agencies and interagency collaborations. This positioned WHO as the lead agency to monitor many of the 43 health-related indicators for the UN Sustainable Development Goals. In 2007, the Institute of Health Metrics and Evaluation (IHME) was established to conduct new global burden of disease and related work, funded by the Bill and Melinda Gates Foundation (BMGF). WHO was a core collaborator in its first GBD2010 study, but withdrew prior to publication as it was unable to obtain full access input data and methods. The publication of global health statistics by IHME resulted in user confusion and in debate over differences and the reasons for them. The new WHO administration of Director General Dr. Tedros Ghebreyesus has sought to make greater use of IHME outputs for its global health statistics and SDG monitoring. Conclusions WHO work on global burden of disease has positioned it to be the lead agency for monitoring many of the UN Sustainable Development Goals. Current moves to use IHME analyses raises a number of issues for WHO and for Member States in relation to WHO's constitutional mandate, its accountability to Member States, the consistency of WHO and UN demographic and health statistics, and the ability of Member States to engage with the results of the complex and computer-intensive modelling procedures used by IHME. As new global health actors and funders have arisen in recent decades, and funding to carry out WHO's expanding mandate has declined, it is unclear whether WHO has the ability or desire to continue as the lead agency for global health statistics.